Kesadaran Beragama pada Remaja Islam - Budiman, Haris (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
The adolescent moment happens as it is seen to be the critical moment of the alteration of character development which is manifested by the negativity of the critical mindset based on factual reality around them that shows a counter reality (ironical paradox) of what has already been said and what has already been done. Manifested as a negativity, the most important thing is the contemplation of the religious faith of the youth, especially the Islamic youth, they tend to be skeptical, anxious and do not have the awareness and no interest in doing various religious activities within solemn deeds.